Acid‐Labile Acyclic Cucurbit[n]uril Molecular Containers for Controlled Release. (7th September 2017) - Mao, Dake; Liang, Yajun; Liu, Yamin; Zhou, Xianhao; Ma, Jiaqi; Jiang, Biao; Liu, Jia; Ma, Da
Abstract: Stimuli‐responsive molecular containers are of great importance for controlled drug delivery and other biomedical applications. A new type of acid labile acyclic cucurbit[ n ]uril (CB[ n ]) molecular containers is presented that can degrade and release the encapsulated cargo at accelerated rates under mildly acidic conditions (pH 5.5–6.5). These containers retain the excellent recognition properties of CB[ n ]‐type hosts. A cell culture study demonstrated that the cellular uptake of cargos could be fine‐tuned by complexation with different containers. The release and cell uptake of cargo dye was promoted by acidic pH. Abstract : Acyclische Cucurbit[ n ]urile (CB[ n ]) sind molekulare Behälter mit hervorragenden Erkennungseigenschaften, die eine eingeschlossene Fracht unter schwach sauren Bedingungen (pH 5.5–6.5) infolge ihres Abbaus beschleunigt freisetzen können. In einer Zellkulturstudie konnte die Frachtaufnahme durch Komplexierung mit verschiedenen Behältern fein eingestellt werden. Freisetzung eines eingelagerten Farbstoffs und dessen Aufnahme durch Zellen waren in saurem Milieu erleichtert.